Cosmetic satisfaction in operative versus non-operative treatment of clavicle fractures: a meta-analysis - Hama, Bawan; Shiruru, Prathik; Naik, Arjun; Koti, Manjunath (International Journal of Research in Orthopaedics, 2026)
Midshaft clavicle fractures are increasingly treated operatively. Functional and union outcomes have been extensively studied, but patient satisfaction with cosmetic appearance is less frequently analysed. A systematic review of PubMed-indexed comparative studies of operative versus non-operative management of displaced midshaft clavicle fractures was performed, with specific focus on patient-reported cosmetic outcomes. Randomised or comparative cohort studies in adults were eligible. The primary endpoint was satisfaction with shoulder appearance. Where dichotomous data were available, risk ratios (RR) with 95% confidence intervals (CI) were calculated. Where cosmetic data were incomplete, results were synthesised narratively. Four adult studies (three randomised trials and one prospective cohort; 409 fractures in total) reported cosmetic outcome data. Only the multicentre root canal therapy (RCT) from the Canadian Orthopaedic Trauma Society (COTS) provided extractable binary data for global cosmetic satisfaction. At one year, 84% (52/62) of patients treated with plate fixation were satisfied with appearance compared with 53% (26/49) in the non-operative group (RR 1.58, 95% CI 1.19-2.10), indicating a 58% relative increase in cosmetic satisfaction with surgery. The RCTs by Robinson et al and Smekal et al both reported significantly higher cosmetic satisfaction in surgically treated patients. The cohort series by Jubel et al described excellent contour restoration and high cosmetic satisfaction after intramedullary fixation. Within the data limitations, operative fixation of displaced midshaft clavicle fractures in adults is associated with higher cosmetic satisfaction than non-operative treatment. Surgery markedly reduces dissatisfaction from bony deformity at the expense of a surgical scar and occasional hardware prominence.